2021
DOI: 10.1088/1674-1056/abd92c
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization evolution and relaxation behavior of high entropy bulk metallic glasses using microalloying process

Abstract: The role of the microalloying process in relaxation behavior and crystallization evolution of Zr20Cu20Ni20Ti20Hf20 high entropy bulk metallic glass (HEBMG) was investigated. We selected Al and Nb elements as minor elements, which led to the negative and positive effects on the heat of mixing in the master HEBMG composition, respectively. According to the results, both elements intensified β relaxation in the structure; however, α relaxation remained stable. By using different frequencies in dynamic mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…This event leads to a competition between entropy (confusion principle) and enthalpy in the glass formation and therefore, an optimum Y addition is attained for the maximum T rg . As presented in figure 6(a), it can be suggested that the Y addition acts as a microalloying process for GFA improvement, which this mechanism was also reported in other high entropy alloying systems [40][41][42]. On the other side, one can observe that Ni, Cu-, V, Ni-and V, Cr-added systems tend to form glasses with the maximum T rg near the equiatomicity condition.…”
Section: New High Entropy Alloying Compositionssupporting
confidence: 60%
“…This event leads to a competition between entropy (confusion principle) and enthalpy in the glass formation and therefore, an optimum Y addition is attained for the maximum T rg . As presented in figure 6(a), it can be suggested that the Y addition acts as a microalloying process for GFA improvement, which this mechanism was also reported in other high entropy alloying systems [40][41][42]. On the other side, one can observe that Ni, Cu-, V, Ni-and V, Cr-added systems tend to form glasses with the maximum T rg near the equiatomicity condition.…”
Section: New High Entropy Alloying Compositionssupporting
confidence: 60%
“…e effects of Al and Nb microalloying process on the dynamic relaxation of Zr 20 Cu 20 Ni 20 Ti 20 Hf 20 high-entropy BMG were also evaluated through the mechanical spectroscopy [24]. e results unveiled that the activation energy of β relaxation for the Nb-added BMG was significantly higher, which was derived from the generation of severe chemical heterogeneity in the atomic structure.…”
Section: Introductionmentioning
confidence: 99%